Pendampingan Penggunaan Aplikasi Marketplace untuk Meningkatkan Omset Penjualan bagi Pelaku UMKM Kuliner Jakarta Pusat - Turangan, Joyce (Prapanca : Jurnal Abdimas, 2023)
Assistance in using the marketplace application to increase sales turnover for culinary Micro, Small, and Medium Enterprises (MSMEs) in Central Jakarta is an effort that aims to help culinary MSMEs take advantage of digital platforms to increase their sales and competitiveness. Through training methods, direct assistance, and preparation of marketing strategies, culinary MSMEs are given the knowledge and skills needed to optimize the use of marketplace applications. The results of this assistance show a significant increase in knowledge, expansion of market reach, increase in sales turnover, and operational efficiency of culinary MSMEs. In conclusion, mentoring the use of the marketplace application plays an important role in helping culinary MSMEs increase their sales turnover, contribute to the growth of the culinary MSME sector, and encourage economic growth in Central Jakarta.